ANALYSIS OF THE CONCEPT OF PROFIT-SHARING PARTNERSHIPS FOR SMALL AND MEDIUM ENTERPRISES AT HOCO COFFEE BANDA ACEH FROM THE PERSPECTIVE OF FIQH MUAMALAH - Hony Khairunnisa Kobat; Analiansyah; Azka Amalia Jihad (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2026)
This study aims to analyse the partnership contract forms between Hoco Coffee Banda Aceh and MSME actors and to review their compliance with the principles of musyarakah in Islamic economics. The study uses a qualitative approach with descriptive-analytical methods through interviews and documentation. The results show that the partnership is implemented through a verbal agreement based on trust (gentleman’s agreement), reinforced by standard operating procedures (SOPs) and a digital recording system, without a formal, legally binding written contract under civil law. In terms of bargaining power, Hoco Coffee has structural dominance because it controls the location, facilities, and payment system. However, MSME partners still have bargaining power through product differentiation and brand strength. This partnership model reflects the concept of musyarakah, in which Hoco contributes non-cash capital, including premises, facilities, and promotion. In contrast, MSMEs contribute operational expertise and products. According to Imam Malik’s view, capital contributions need not be in cash; such partnership practices are valid as long as the distribution of profits and responsibilities is clearly agreed upon. This study concludes that the partnership between Hoco Coffee and MSMEs is collaborative, semi-symmetrical, and substantially consistent with sharia principles on capital contributions and profit sharing.